The Oncogenic Effects, Pathways, and Target Molecules of JC Polyoma Virus T Antigen in Cancer Cells - Zheng, Hua-Chuan; Xue, Hang; Jin, Yu-Zi; Jiang, Hua-Mao; Cui, Zheng-Guo (Frontiers in Oncology, 2022)
JC polyoma virus (JCPyV) is a ubiquitous polyoma virus that infects the individual to cause progressive multifocal leukoencephalopathy and malignancies. Here, we found that T-antigen knockdown suppressed proliferation, glycolysis, mitochondrial respiration, migration, and invasion, and induced apoptosis and G2 arrest. The reverse was true for T-antigen overexpression, with overexpression of Akt, survivin, retinoblastoma protein, β-catenin, β-transducin repeat-containing protein (TRCP), and inhibitor of growth (ING)1, and the underexpression of mammalian target of rapamycin (mTOR), phosphorylated (p)-mTOR, p-p38, Cyclin D1, p21, vascular endothelial growth factor (VEGF), ING2, and ING4 in hepatocellular and pancreatic cancer cells and tissues. In lens tumor cells, T antigen transcriptionally targeted viral carcinogenesis, microRNAs in cancer, focal adhesion, p53, VEGF, phosphoinositide 3 kinase-Akt, and Forkhead box O signaling pathways, fructose and mannose metabolism, ribosome biosynthesis, and choline and pyrimidine metabolism. At a metabolomics level, it targeted protein digestion and absorption, aminoacryl-tRNA biosynthesis, biosynthesis of amino acids, and the AMPK signal pathway. At a proteomic level, it targeted ribosome biogenesis in eukaryotes, citrate cycle, carbon metabolism, protein digestion and absorption, aminoacryl-tRNA biosynthesis, extracellular-matrix-receptor interaction, and biosynthesis of amino acids. In lens tumor cells, T antigen might interact with various keratins, ribosomal proteins, apolipoproteins, G proteins, ubiquitin-related proteins, RPL19, β-catenin, β-TRCP, p53, and CCAAT-enhancer-binding proteins in lens tumor cells. T antigen induced a more aggressive phenotype in mouse and human cancer cells due to oncogene activation, inactivation of tumor suppressors, and disruption of metabolism, cell adhesion, and long noncoding RNA-microRNA-target axes.